Anticoagulants used in plasma collection affect adipokine multiplexed measurements. (April 2016) - Allione, Alessandra; Di Gaetano, Cornelia; Dani, Nadia; Barberio, Davide; Sieri, Sabina; Krogh, Vittorio; Matullo, Giuseppe
Highlights: Monitoring adipokine variation is critical to understand metabolic diseases. We determined the effect of anticoagulants on adipokine levels in plasma samples. IL6, leptin, CRP, adiponectin showed significantly higher levels in LiEp plasma. Adipokine levels in different plasma samples highly correlated each other. Abstract: Obesity is an important health problem worldwide. Adipose tissue acts as an endocrine organ that secretes various bioactive substances, called adipokines, including pro-inflammatory biomarkers such as TNF-α, IL-6, leptin and C-reactive protein (CRP) and anti -inflammatory molecules such as adiponectin. The deregulated production of adipokines in obesity is linked to the pathogenesis of various disease processes and monitoring their variation is critical to understand metabolic diseases. The aim of this study was to determine the plasma concentration of adipokines in healthy subjects by multiplexed measurements and the effect of anticoagulants on their levels. Plasma samples from 10 healthy donors were collected in two different anticoagulants (sodium citrate or heparin). All markers, excluding TNF-α, showed significantly higher concentrations in heparinized compared to citrate plasma. However, levels of adipokines in different plasma samples were highly correlated for most of these markers. We reported that different anticoagulants used in the preparation of the plasma samples affected the measurements of some adipokines. The importance of the present results in epidemiology is relevant when comparing different studies in which blood samples were collected with different anticoagulants.